Genome-wide insights into the development and function of thermogenic adipocytes - Loft, Anne; Forss, Isabel; Mandrup, Susanne (Trends in endocrinology and metabolism, 2017)
Brown and brown-like adipocytes are specialized adipocytes with a high capacity to convert metabolic energy to heat. This function is not only eminent in supporting organismal thermogenesis, but may also have potential in the fight against obesity. The latter has spurred a massive interest in understanding the development and regulation of these thermogenic adipocytes. Here, we review how genome-wide studies based on next-generation sequencing have provided insight into how the chromatin and transcriptional landscapes are established in thermogenic adipocytes and how thermogenic signals can change the genomic programming of white adipocytes. Furthermore, we discuss how the integration of genomic data can be used to discover novel transcriptional pathways that may be modulated as part of therapeutic strategies for the treatment of obesity.
Gesehen am 05.06.2018